Dziecko w przestrzeniach języka ojczystego – wybrane aspekty - Kuszak, Kinga (Wydawnictwo Naukowe UAM, 2016)
The article discusses various spaces of children’s linguistic functioning and the wealth of linguistic experiences available in each of them. The author points to the fact that each of these spaces provides children with different vital experiences. The starting point for the reflections on the spaces of native language is Ferdinand de Saussure’s concept of speech as a human ability and language as a set of forms of speech uses. The term “linguistic space” and the criteria for determining a space were adopted from the works of Kwiryna Handke who emphasized that language, as an integral structural component of social space and the community that uses it, plays two roles in this space: it reflects the community’s perception of its surroundings and provides help and basic tool for shaping the space. Therefore, the forms of language use differ according to the spaces, situations and roles which one encounters. The next part of the paper presents selected vocabulary that children may potentially acquire in the following spaces: family, kindergarten (school), peer group, via Internet communication, as viewers of TV commercials and readers (recipients) of literature. The summary presents the spaces of children’s linguistic functioning in the form of a chart, taking into account the roles adopted by children in each space, places and situations distinctive of the space, as well as the words, expressions, and language tools typical for each space.
Children in the Space of their Native Language – Selected Aspects
Keywords: child; native language; language acquisition; child’s linguistic experiences; ocabulary expansion